0D/2D CeO2/BiVO4 S-scheme photocatalyst for production of solar fuels from CO2. (1st February 2023) - Geng, Jiguo; Guo, Shixun; Zou, Zongyan; Yuan, Zhenzhou; Zhang, Dong; Yan, Xiaotong; Ning, Xuefeng; Fan, Xiujun
Graphical abstract: Highlights: Effective S-scheme Ce@BiVO4 nanocomposite photocatalyst. Efficient conversion of CO2 into significant yields of hydrocarbon fuels. Sufficient basic sites at CeO2 surface making CeBV-20 nanocomposite effective for CO2 adsorption. High separation of charge carriers identified by PL analysis in the final nanocomposite. Highly stable and reused up to five consecutive recycling runs. Abstract: The production of hydrocarbon fuels is essential for the energy market to develop a green and sustainable environment. However, new pathways are being developed to accelerate energy production to fulfill energy demands. Here, we have developed an efficient 0D/2D CeO2 /BiVO4 S-scheme heterojunction for producing methanol from CO2 in visible illuminance. The developed heterojunction photocatalyst demonstrated the excellent yield of methanol and the production of CO and CH4 in small amounts. The high yield of methanol refers to the effective charge separation and good basic sites at the heterojunction photocatalyst due to the CeO2 content, which facilitates the accommodation of CO2 molecules more efficiently at the CeO2 surface and provides a higher yield of methanol than CeO2 and BiVO4 alone. In addition, the effective charge separation between CeO2 and BiVO4 provided excellent yields of C1 solar fuels. The characteristic properties of the synthesized photocatalysts were examined using various spectroscopic and microscopic techniques. Also, the recovered photocatalyst exhibited relatively similar activity without leaching the metal content after five consecutive runs under identical experimental conditions.